Reciprocal recurrent selection based on genetic complementation: An efficient way to build heterosis in diploids due to directional dominance - Covarrubias Pazaran, Giovanny Eduardo; Werner, Christian R.; Gemenet, Dorcus C. (Wiley, 2023)
Depending on the trait architecture and reproduction system, selection strategies in plant breeding focus on the accumulation of additive, dominance effects, or both. Innovation in the exploitation of dominance‐effect‐based heterosis has been limited since the proposal of general combining ability (GCA)‐based approaches. We propose the use of a new surrogate of genetic complementation between genetic pools to increase accumulation of dominance effects and heterosis. We simulated breeding programs to show how reciprocal recurrent selection (RRS) by genetic complementation would build the dominance‐based heterosis cheaper than GCA‐based approaches and used real phenotypic data from hybrid maize ( Zea mays ) to demonstrate the underlying concepts. We found RRS by genetic complementation to be an attractive and viable strategy to exploit dominance, build de novo heterotic pools, and enhance the current GCA‐based approaches. If demonstrated in practice, we hypothesized that this approach would lower the cost of hybrid breeding drastically and contribute to food security.